Guidelines for Integrating Creative Movement : A Case Study of Private School - Supalaiwat, Supasuta; Khayankij, Sasilak (An Online Journal of Education, 2023)
The primary aim of this research was to explore the strategies employed by kindergarten teachers in the integration of creative movement within their classroom settings. The study focused on a sample of 36 kindergarten teachers at Jitmhetta Kindergarten Classroom (Pseudonym), a private school, and utilized a questionnaire as the primary research instrument. The data collected through the questionnaire was analyzed using statistical techniques, such as frequency distribution, percentages, and content analysis. The findings of the study indicated that the successful incorporation of creative movement in the classroom was contingent upon the teachers' knowledge, creativity, and willingness to include movement in their lessons. The study proposed two key approaches: firstly, the planning and implementation of sequential activities with clear objectives and appropriate movement media, such as song, rhythm, and rhymes while ensuring the safety and suitability of movements within the classroom space. Secondly, the organization of group activities that encourage children to engage in free movement, characterized by clear rhythms aligned with learning objectives, followed by calming activities that involve stretching and relaxation. These approaches have the potential to enhance children's physical and emotional development, as well as cultivate a positive classroom environment.